2003
DOI: 10.4049/jimmunol.171.1.390
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Airway Hyporesponsive C3H/HeJ Mice Express a Unique Isoform of the Signaling Protein Ras Guanine Nucleotide Releasing Protein 4 That Is Unresponsive to Diacylglycerol and Phorbol Esters

Abstract: cDNAs were recently isolated from BALB/c mouse mast cells (MCs) that encode the new signaling protein mouse Ras guanine nucleotide releasing protein 4 (mRasGRP4). The present study evaluates the expression pattern and biological activity of mRasGRP4 in a variety of mouse strains. As assessed immunohistochemically and by RNA analysis, mRasGRP4 is not coordinately expressed with any of its family members. Normally, mRasGRP4 is an MC-restricted protein in tissues, and kinetic studies revealed that mRasGRP4 is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Immunogold ultrastructural studies of the in vivo differentiated MCs in the V3 mastocytosis mouse revealed that RasGRP4 tends to reside either in the cytoplasm or on the cytosolic side of the plasma membrane (4). The latter data imply that RasGRP4 participates in early signaling events at the surface of the MC with an undefined receptor.…”
Section: Mast Cells (Mcs)mentioning
confidence: 81%
See 2 more Smart Citations
“…Immunogold ultrastructural studies of the in vivo differentiated MCs in the V3 mastocytosis mouse revealed that RasGRP4 tends to reside either in the cytoplasm or on the cytosolic side of the plasma membrane (4). The latter data imply that RasGRP4 participates in early signaling events at the surface of the MC with an undefined receptor.…”
Section: Mast Cells (Mcs)mentioning
confidence: 81%
“…The ϳ19-kb mouse RasGRP4 gene was isolated and mapped to chromosome 7B1 (4). Its human (3) and rat (5) orthologs were then isolated using homology-based cloning approaches.…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…These mice express a dysfunctional RasGRP4 protein that lacks a DAG-binding domain. Consequently, they are hyporesponsive to methacholine stimulation (14). We further analyzed why these RasGRP4 Ϫ/Ϫ mast cells are hyporesponsive to stimulation and found that Fc⑀RI-mediated Erk and p38 activation was reduced, whereas activation of other signaling events was not largely affected.…”
Section: Discussionmentioning
confidence: 99%
“…Its function in mast cells was suggested from studies with C3H/HeJ mice, which are hyporesponsive to methacholine stimulation via the airway (14). These mice express a dysfunctional RasGRP4 protein that lacks a DAG-binding domain (C1 domain) because of aberrant splicing.…”
Section: Ras Guanine Nucleotide-releasing Protein (Rasgrp)mentioning
confidence: 99%